Marine enzymes and food industry: insight on existing and potential interactions - Fernandes, Pedro (Frontiers in Marine Science, 2014)
Evidence that support the marine environment as source of useful biocatalysts for application in several areas of industry pile up, both as scientific reports or patent applications. Marine microorganisms have to endure habitats characterized by extreme conditions of salinity, temperature or pressure. Their enzymes present concomitant features, viz. thermostability or halostability, which are appealing for practical applications. The food sector is a field where enzymes are used, given their specificity, compliance with strict regulations, relatively mild operational conditions required and environmental friendly nature. The specific features presented by marine enzymes can be advantageously used both for process improvement or to develop new processes and products. In the present review the role of relevant types of enzymes for the food sector is described and recent findings on those enzymes from marine are put into context. The information provided is illustrative that in spite of the relative novelty concerning the use of marine enzymes within the scope of the food sector, some processes have reached commercial status and promising results are being obtained with several others. Moreover, there is still a vast field of resources for enzyme activity to be explored, namely since the screening process that has been considerably improved with the contribution of metagenomic libraries. It can thus be considered that future and exciting developments can be expected concerning the use of marine enzymes in the food and feed areas.